Molecular and Cellular Events Mediating Glomerular Podocyte Dysfunction and Depletion in Diabetes Mellitus - Anil Kumar, P.; Welsh, Gavin I.; Saleem, Moin A.; Menon, Ram K. (Frontiers in Endocrinology, 2014)
The essential function of the kidney is to ensure formation of relatively protein-free ultra-filtrate, urine. The rate of filtration and composition of the primary renal filtrate is determined by the transport of fluid and solutes across the glomerular filtration barrier consisting of endothelial cells, the glomerular basement membrane, and podocyte foot processes. In diabetes mellitus (DM), components of the kidney that enable renal filtration get structurally altered and functionally compromised resulting in proteinuria that often progresses to end stage renal disease. Histological alterations in DM include early hypertrophy of glomerular and tubular components, subsequent thickening of basement membrane in glomeruli and tubules, progressive accumulation of extracellular matrix proteins in the glomerular mesangium and loss of podocytes, together constituting a clinical condition referred to as diabetic nephropathy (DN). The glomerulus has become the focus of research investigating the mechanism of proteinuria. In particular the progressive dysfunction and/or loss of podocytes that is contemporaneous with proteinuria in DN have attracted intense scientific attention. The absolute number of podocytes predicts glomerular function and podocyte injury is a hallmark of various glomerular diseases. This review discusses the importance of podocytes in normal renal filtration and details the molecular and cellular events that lead to podocyte dysfunction and decreased podocyte count in DN.